Measurement and urban-rural disparity of multidimensional health poverty among Chinese households: a CFPS data analysis - Yongqiang LAI; Ye LI; Xinwei LIU; Qunhong WU; Lijun GAO; Zheng KANG; Huan LIU; Yulu TIAN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo measure multidimensional health poverty (MHP) and its urban-rural disparity among Chinese households for providing evidence to the elimination of health poverty among urban and rural households in China. MethodsThe data of the analysis were extracted from a round of China Family Panel Survey (CFPS) conducted in 2018 across China, which collected the information of 12 494 households (6 409 in urban and 6 085 in rural regions) on economic activity, education access, family relationship and dynamics, migration, and family members' physical and mental health status. The MHP was assessed and the contribution of the three dimensional components (health right, health capability and health risk) to MHP were deconstructed with self-established health poverty evaluation index system and multidimensional health poverty measurement index (MHPI). ResultsFor all the households surveyed in 2018, the overall MHPI was 0.216 and the prevalence of MHP was 0.472; the values of MHPI and MHP prevalence were 0.184 and 0.410 for the surveyed urban households but were 0.249 and 0.537 for the rural households. For the households surveyed nationwide, in urban regions, and in rural regions, the contribution indexes of health risk/capability/right to MHP were 0.478/0.268/0.254, 0.267/0.268/0.505, and 0.244/0.299/0.457, respectively. ConclusionDuring 2018 in China, both the MHPI and MHP prevalence were higher in rural households than those in urban households; health risk was an important contributor to MHP and the urban-rural disparity in the contribution of health capacity to MHP was the greatest among the three dimensional contributors of MHP.